Higher education students: barriers to engagement; psychological alienation theory, trauma and trust: a systematic review. (3rd April 2021) - Jones, Caroline S.; Nangah, Zoë
ABSTRACT: This paper is a systematic review of the UK Widening Participation (WP), Higher Education (HE) student demographic. It argues that the presence of traumatic emotional experiences in WP student populations connected to psychosocial and academic trust alienation theory contributes to engagement barriers in HE. Using PRISMA guidelines, 43 publications were screened based on inclusion/exclusion criteria. This paper identifies WP students' experiences of trauma and how this affects their HE educational engagement. Secondly, it encourages the HE community to consider commitment to the WP demographic. Thirdly it identifies support strategies for WP student success and improvements for HE Institutions (HEI's) commitment to meeting WP agendas. Additionally, educational and psychological links that have not previously been examined are presented acknowledging the complexities of the WP student demographics. Furthermore, reinforcement for HEI's commitment to social mobility from both a political and institutional standpoint aligning to the WP student demographic barriers to engagement is articulated.